Instructional Leadership Challenges in Public Secondary Schools in Sudan - Hamad, Ismail; Demissie, Getnet; Darge, Reda (Technium Social Sciences Journal, 2021)
The study aimed to investigate Instructional Leadership Challenges in Public Secondary Schools in Sudan, North Kordufan State; Shekan Locality (Elobeid city). In order to achieve the objectives of the study, a descriptive survey method was employed. The population of the study was 451 teachers and 12 Principals. From this population, 222 teachers and 12 principals were used as a sample using simple random and comprehensive sampling techniques. Data collected from respondents were analyzed and interpreted using percentages, a one-sample t-test, and a weighted mean. The findings revealed that there are significant challenges for instructional leadership such as school dropout due to the living and economic conditions and the delay of some teachers for classes because of transportation. Lack of financial support has been a cause for inadequate educational facilities and laboratories and a poor school environment. On top of the findings, recommendations are forwarded to address the gaps encountered in the instructional leadership practices which mainly focusing on empowering principals, teachers, and schools.